2022
DOI: 10.2196/15719
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Indian Obesity-Related mHealth Apps: PRECEDE-PROCEED Model–Based Content Analysis

Abstract: Background The prevalence of obesity in India is increasing at an alarming rate. Obesity-related mHealth apps have proffered an exciting opportunity to remotely deliver obesity-related information. This opportunity raises the question of whether such apps are truly effective. Objective The aim of this study was to identify existing obesity-related mHealth apps in India and evaluate the potential of the apps’ contents to promote health behavior change. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Despite a wealth of literature on mHealth apps in general and user-generated app reviews in particular, research on the relationship between prescription and reimbursement and user experience is still in its infancy. A significant body of research focuses on a qualitative, clinical evaluation of mHealth apps in Germany, centering around physician's/healthcare practitioners' perspectives of mHealth apps [9][10][11][12] , whereas international publications have focused predominantly on app development issues 20,21 , and feature evaluation [22][23][24] to make mHealth apps more accessible and user-friendly. While certification has been a theme researched in the context of mHealth apps 8 , there simply has been no real-world data comparing the user experience with regulated mHealth apps to that with their consumer counterparts, as such apps did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a wealth of literature on mHealth apps in general and user-generated app reviews in particular, research on the relationship between prescription and reimbursement and user experience is still in its infancy. A significant body of research focuses on a qualitative, clinical evaluation of mHealth apps in Germany, centering around physician's/healthcare practitioners' perspectives of mHealth apps [9][10][11][12] , whereas international publications have focused predominantly on app development issues 20,21 , and feature evaluation [22][23][24] to make mHealth apps more accessible and user-friendly. While certification has been a theme researched in the context of mHealth apps 8 , there simply has been no real-world data comparing the user experience with regulated mHealth apps to that with their consumer counterparts, as such apps did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…The two reviewers (PMS and LK) discussed uncertainties regarding the reviewed applications, and if they could not agree, the third reviewer (SAMM) was consulted to reach a consensus. The assessment was methodically adapted from similar studies ( 28 , 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…recorded number of downloads, sample size, median and interquartile range (IQR) for each score (ORCHA, UX, PCA and DP) when separated by assigned download level (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The sample size for download levels varied from 0 to 177 health apps.…”
Section: Plos Onementioning
confidence: 99%
“…In line with this, previous studies have shown that app quality ratings are often not significantly positively associated with user ratings. For instance, user ratings were found not to be significantly correlated with Mobile Application Ratings Scale (MARS) scores [ 16 , 17 ] or ‘PsyberGuide credibility ratings scale’ (PGCRS) scores [ 18 ]. A study from 2022 [ 19 ], found a weak but significant negative correlation between their criteria and scores and user ratings for women with anxiety during pregnancy.…”
Section: Introductionmentioning
confidence: 99%